Perancangan Alat Kontrol Suhu Ruangan dan Detektor Gerak Berbasis IoT dengan Menggunakan Arduino dan Cayenne - Tuti Hartati; Susanto Susanto (LPPM STMIK AMIK BANDUNG, 2019)
The development of technology towards IoT or the Internet of Things has been very advanced so that the fulfillment of humanneeds is increasingly easy and comfortable. One example is the need to control and monitor the air temperature in the server room. Theserver room requires a cool and stable temperature so that the computer devices inside can function properly. In addition, the roomalso requires a security system to prevent undesirable things, such as intruders or people who are other than server admin officers.These needs can be fulfilled by creating an IoT-based device. Arduino as the main device and online Cayenne web-based application asa medium for controlling Arduino. This device is equipped with a motion detection security system using the PIR Motion Detector HCSR501sensor while for temperature monitoring using a DHT22 sensor. Control of tools can be done using a web browser on a PC(Personal Computer) and an android smartphone via an internet connection